Low-cost vacuum-assisted closure dressing in wound management: An effective alternative for Nepal - Bajracharya, Amir (Journal of Kathmandu Medical College, 2022)
Background: Low-cost vacuum-assisted closure (VAC) can be used as an alternative method for wound management. Objectives: To observe the effectiveness of low-cost vacuum-assisted closure dressing in wound management. Methods: A descriptive cross-sectional hospital-based study was conducted in the Department of Plastic Surgery, Kathmandu Medical College from April 2021 to February 2022 to observe age, sex, indication, type of wound with history of comorbidities, number of dressings, duration of hospital stays, and complications like: bleeding, haematoma, and delay in wound healing . Results: A total of 22 patients were included by convenience sampling technique in the study with 21 (95.5%) acute and one (4.5%) case of chronic wound with ulcer. The mean age was 39 ± 18.157 years ranging from 13-76 years. Most of them were males (15, 68.2%). The mean duration of wound presentation was 5.45 ± 9.127 days ranging from 1-45 days. The mean duration of hospitalisation was 20.45 ± 11.467 days ranging from 5-45 days. Eight (36.4%) patients were with comorbidities like Diabetes Mellitus, Hypertension, Peripheral vascular diseases etc., and no mortality was recorded. Conclusion: Low-cost Vacuum-assisted closure is a very easy and efficient alternative method for wound care.